2013
DOI: 10.1111/cdev.12177
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Interviewer Support, and Children's Eyewitness Identification Accuracy

Abstract: Few studies have investigated how stress affects eyewitness identification capabilities across development, and no studies have investigated whether retrieval context in conjunction with stress affects accuracy. In this study, one hundred fifty-nine 7- to 8- and 12- to 14-year-olds completed a high- or low-stress laboratory protocol during which they interacted with a confederate. Two weeks later, they attempted to identify the confederate in a photographic lineup. The lineup administrator behaved in either a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 70 publications
2
31
0
Order By: Relevance
“…In children and adolescents, laboratory-based protocols inspired by the TSST have been used to link acute stress reactivity to numerous events and processes, including child maltreatment (Seltzer et al, 2013; Trickett et al, 2014), later memory recall (Rush et al, 2013), allergic asthma symptoms (Buske-Kirschbaum, 2003), rumination and depressive response styles (Stewart et al, 2013), pubertal development (van den Bos et al, 2013), or body mass index (Francis et al, 2013). The broad range of research problems approached using TSST variants is not surprising given the well-documented associations between individual differences in stress reactivity and socio-emotional, cognitive, or physical development outcomes (Gunnar and Quevedo, 2007).…”
Section: Advantages Of Laboratory-based Social Stress Paradigms For Imentioning
confidence: 99%
“…In children and adolescents, laboratory-based protocols inspired by the TSST have been used to link acute stress reactivity to numerous events and processes, including child maltreatment (Seltzer et al, 2013; Trickett et al, 2014), later memory recall (Rush et al, 2013), allergic asthma symptoms (Buske-Kirschbaum, 2003), rumination and depressive response styles (Stewart et al, 2013), pubertal development (van den Bos et al, 2013), or body mass index (Francis et al, 2013). The broad range of research problems approached using TSST variants is not surprising given the well-documented associations between individual differences in stress reactivity and socio-emotional, cognitive, or physical development outcomes (Gunnar and Quevedo, 2007).…”
Section: Advantages Of Laboratory-based Social Stress Paradigms For Imentioning
confidence: 99%
“…The act of retrieving memories of distressing experiences itself may induce arousal, especially for children of parents who tend toward greater insecurity in their attachment representations. Arousal at retrieval is known to decrease memory performance (Almerigogna, Ost, Akehurst, & Fluck, 2008; Quas & Lench, 2007; Rush et al, 2013). In the present study, children were asked to recall story narratives that they had previously made up.…”
Section: Discussionmentioning
confidence: 99%
“…In others, children have been interviewed by a positive and emotionally supportive versus a neutral and emotionally distant interviewer (Carter, Bottoms, & Levine, 1996; Davis & Bottoms, 2002; Quas, Bauer, & Boyce, 2004). Children are more accurate and less susceptible to false suggestions when questioned in a supportive than non-supportive context (Carter et al, 1996; Goodman, Bottoms, Schwartz-Kenney, & Rudy, 1991; Quas, Wallin, Papini, Lench, & Scullin, 2005; Rush et al, 2013). …”
mentioning
confidence: 99%
“…Studies have consistently shown that greater arousal during the retrieval of memories inhibits memory (Roozendaal et al 2009;Smeets et al 2008) and being interviewed at a Barnahus may reduce stress and make children more comfortable in the interview setting. This in turn may allow them to use cognitive resources to make a memory search and/ or focus on the interviewer's questions (Goodman et al 2014;Quas et al 2004;Rush et al 2014). The RP particularly highlights the importance of interviewers responding more sensitively and using supportive comments with reluctant children (Ahern et al 2014).…”
Section: The Revised Nichd Protocolmentioning
confidence: 99%